(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives:To investigate factors affecting the essential competencies of pediatric nurse managers at 3 provincial and national pediatric hospitals in Vietnam in 2023. Participants and Methods: Qualitative research was conducted at three provincial and national pediatric hospitals in Vietnam with 14 in-depth interviews and sixfocus group discussions with a maximum of 6 participants per group. Data collection was conducted in 2022-2023. Data analysis was performed using Mindjet Mindmanager software. Results: The head nurse spent approximately 10 years preparing to accumulate clinical knowledge and skills, communication skills, hospital environment preparation and support were all major factors influencing the competence of the pediatric head nurse. Conclusions and recommendations: The preparation time of 10 years, the requirement to accumulate clinical knowledge and skills, communication and leadership skills are important factors. In addition, the working environment and supportive culture of the leadership are the main influencing factors. The results of this study can be used to provide information as evidence for policy makers on training essential competencies of the pediatric nursing workforce to build a training program to upgrade the level of head nurses to provide high-quality care for pediatric patients in Vietnam.